Pemberian ekstrak etanol Cordyceps militaris dapat menurunkan kadar glukosa darah dan menghambat penurunan massa sel beta pankreas pada tikus diabetes mellitus yang diinduksi dengan Streptozotocin dan Nikotinamid - Jopy Wikana (DiscoverSys Inc., 2018)
Background: The antioxidant and anti-inflammatory effects of Cordyceps militaris extracts can neutralize the increased production of Reactive Oxygen Species (ROS) due to hyperglycemia conditions, as well as neutralize NO produced through inducible Nitric Oxide Synthase (iNOS). Thus, the antioxidant effects of C. militaris extract are expected to decrease DNA damage and ER stress leading to intrinsic apoptosis of pancreatic beta cells. Another positive effect of C. militaris which is expected to suppress glucotoxicity is its hypoglycemic effect.Methods: The design of this study was Randomized Post-test Only Control Group Design. The study was conducted on mice divided into three groups: negative control group (DM + placebo), treatment 1 group and treatment 2 group.Results: Based on study on 15 rats, each 5 rats per group, it was found that the mean blood glucose level in control group was 399,20 ± 28,07 mg/dl, mean of blood glucose level of treatment 1group (extraction 50% ethanol Cordyceps militaris) was 198.60 ± 30.42 mg/dl, and, the mean blood glucose levels of the treatment 1 group (extract ethanol Cordyceps militaris 100%) was 141.00 ± 17.03 mg/dl. With One Way ANOVA test found that p-value = 0,001. Immunohistochemical examination result shows that beta cell mass is more prominent in either treatment group 1 and treatment group 2 compare to the control group.Conclusions: There were significant differences in blood glucose levels after extracted ethanol Cordyceps militaris. It is further known that ethanol extract of Cordyceps militaris can decrease blood glucose level by 50,25% at 50% concentration and 64,68% at 100% concentration. Immunohistochemical examination result shows that ethanol extract of C. militaris seem could inhibit the decrease of beta cell mass especially at 100% concentration.